2016
DOI: 10.1002/ange.201511361
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing Identifies Inhibitors of Oseltamivir‐Resistant Influenza Viruses

Abstract: The inhibitor of neuraminidase (NA), oseltamivir, is a widely used anti-influenza drug. However, oseltamivir-resistant H1N1 influenza viruses carrying the H275Y NA mutation spontaneously emerged as a result of natural genetic drift and drug treatment. Because this and other potential mutations may generate a future pandemic influenza strain that is oseltamivir-resistant, alternative therapy options are needed. Here show that a structure-based computational method can be used to identify existing drugs that inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Clarithromycin and naproxen À along with oseltamivir in a three-drug combinationhave been evaluated in a phase 2b/3 clinical trial that showed efficacy in the treatment of severe influenza [56]. Also, nalidixic acid and dorzolamide were identified by an in silico screening specifically targeting mutant viral neuraminidase and showed efficacy against oseltamivir-resistant influenza, but not against wild-type viruses [57]. Perhaps the most advanced example of DR is the case of the antiparasitic drug nitazoxanide, which is a safe drug used for the treatment of Giardia and Cryptosporidium spp.…”
Section: Influenza Virusmentioning
confidence: 99%
“…Clarithromycin and naproxen À along with oseltamivir in a three-drug combinationhave been evaluated in a phase 2b/3 clinical trial that showed efficacy in the treatment of severe influenza [56]. Also, nalidixic acid and dorzolamide were identified by an in silico screening specifically targeting mutant viral neuraminidase and showed efficacy against oseltamivir-resistant influenza, but not against wild-type viruses [57]. Perhaps the most advanced example of DR is the case of the antiparasitic drug nitazoxanide, which is a safe drug used for the treatment of Giardia and Cryptosporidium spp.…”
Section: Influenza Virusmentioning
confidence: 99%
“…A three drug combination of Clarithromycin and naproxen along with oseltamivir showed efficacy in the treatment of severe influenza. 29 Nalidixic acid and dorzolamide showed efficacy against oseltamivirresistant influenza by an in silico screening specifically targeting mutant viral neuraminidase and, 30 the most advanced example of DR is the case of the antiparasitic drug nitazoxanide, currently being repurposed for the treatment of influenza. 31 The kinase inhibitors namely dinaciclib, flavopiridol and PIK-75 were reported to be highly effective against the H7N9 virus with less toxicity.…”
Section: Repurposing In Influenza and Denguementioning
confidence: 99%
“…The most common reason for repurposing is that approved drugs have already been tested for safety in humans, meaning they should enter the clinic quickly . As discussed in Section , many older drugs, even those with known serious side effects, have indeed been reintroduced to the clinic for purposes beyond their original indications.…”
Section: Introductionmentioning
confidence: 99%